Vivendo à sombra das Leis: Antonio Soares Brederode entre a justiça e a criminalidade. Capitania da Paraíba (1787-1802) - Paiva, Yamê Galdino de (2012)
Assuming Ouvidoria of Paraíba for ten years, Antonio Felipe Soares de Andrada de Brederode has been responsed for a great number of letters and occupations sent to Conselho Ultramarino, available, nowadays, by the Project Rescue Baron of Rio Branco. Accused of involving with several business types, extorting the richest men of the comarca and abuse of power, Antonio Brederode promoted serious tensions in the power s relationships existent in the captaincy. Using the theoretical referencial of the New Political History, the present work aimes to observe the practices of this ouvidor under the lens of the Political Culture of portuguese Ancient Regime. Through this study, it is intended to understand a little about how the Ouvidoria of Paraíba worked, as well as to introduce the officials responsible for the justice s administration. It is also aimed, through the alliances with and against Antonio Brederode, to identify the groups which used to hold the economical and political power of the captaincy and their relation to the ouvidor.